2007
DOI: 10.1148/radiol.2423051191
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Willis at CT Angiography: Dose Reduction and Image Quality—Reducing Tube Voltage and Increasing Tube Current Settings

Abstract: In head phantoms, lower tube voltage improved SNR at equal radiation doses. For CT angiography of the circle of Willis, this translated into superior image quality at 90 kVp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 14 publications
11
82
0
Order By: Relevance
“…In this phantom, the mean CT number of brain parenchyma was approximately 33 HU in all images of the cerebrum level at 120 kV. The mean attenuation for brain parenchyma of the patients is reportedly 35 HU in CTA at 120 kV [17]. The mean CT numbers for the internal carotid artery of 20 patients were 340 ¡ 60.1 HU at 90 kV and 253 ¡ 46.3 HU at 120 kV in CTA [17].…”
Section: Tube Voltage and Effective Masmentioning
confidence: 81%
“…In this phantom, the mean CT number of brain parenchyma was approximately 33 HU in all images of the cerebrum level at 120 kV. The mean attenuation for brain parenchyma of the patients is reportedly 35 HU in CTA at 120 kV [17]. The mean CT numbers for the internal carotid artery of 20 patients were 340 ¡ 60.1 HU at 90 kV and 253 ¡ 46.3 HU at 120 kV in CTA [17].…”
Section: Tube Voltage and Effective Masmentioning
confidence: 81%
“…-cerebral CT angiography [30,31] -pulmonary CT angiography [32][33][34] -aorto-iliac CT angiography [8,35,36] • Lowering of the tube voltage and/or tube current for non-contrast CT [37] • Reduction of the total number of imaging phases (e.g. split-bolus technique) [38,39] • Adjustment of image quality reference values of the automatic tube current modulation for oversized patients [40] • Reduction of the tube voltage and/or tube current for survey CT [41,42] • Positioning of the X-ray tube below the table for the survey CT (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent research has demonstrated the potential use of dual-energy CT (DECT) and different tube voltage/ tube current protocols for the characterization of tissue components and organ perfusion as well as for dose reduction [5][6][7][8][9][10][11]. In addition there is evidence that suggests the usefulness of DECT for comprehensive imaging of coronary artery disease and the evaluation of myocardial perfusion [12,13].…”
Section: Introductionmentioning
confidence: 99%